Aggregation‐Enhanced Emission and Thermally Activated Delayed Fluorescence of Derivatives of 9‐Phenyl‐9H‐Carbazole: Effects of Methoxy and tert‐Butyl Substituents. Issue 38 (8th June 2018) - Grybauskaite‐Kaminskiene, Gintare; Volyniuk, Dmytro; Mimaite, Viktorija; Bezvikonnyi, Oleksandr; Bucinskas, Audrius; Bagdziunas, Gintautas; Grazulevicius, Juozas V.
Abstract: Derivatives of 9‐phenyl‐9 H ‐carbazole were synthesized as efficient emitters exhibiting both thermally activated delayed fluorescence and aggregation‐induced emission enhancement. Effects of methoxy and tert ‐butyl substituents at the different positions of carbazolyl groups on the properties of the emitters were studied. Depending on the substitutions, photoluminescence quantum yields (PLQY) of non‐doped solid films of the compounds ranged from 17 % to 53 % which were much higher than those observed for the solutions in low‐polarity solvent toluene. Compounds substituted at C‐3 and C‐6 positions of carbazole moiety by methoxy‐ and tert ‐butyl‐ groups showed the highest solid‐state PLQY. Ionization potentials of the studied derivatives in solid‐state were found to be in the short range of 5.75–5.89 eV. Well‐balanced hole and electron mobilities were detected for tert ‐butyl‐substituted compound. They exceeded 10 −4  cm 2  (V×s) −1 at electric fields higher than 3×10 5  V cm −1 . Two compounds with the highest solid‐state PLQYs showed higher efficiencies in non‐doped organic light‐emitting diodes than in the doped devices. Maximum external quantum efficiency of 7.2 % and brightness of 15000 cd m −2 were observed for the best device. Abstract : Aggregation induced enhanced emission and thermally activated delayed fluorescence effects were identified for four new emitters resulting in the efficient emission of their non‐doped solid layers. It was shown that efficiency of delayed fluorescence can be increased by attachment of methoxy and tert ‐butyl substituents. Blue and green organic light‐emitting diodes with non‐doped light‐emitting layers were fabricated by using these emitters. Maximum external quantum efficiency and brightness values of 7.2 % and 15 000 cd m −2, respectively, were observed for the best device.